Skip Segment Hirschsprung Disease Managed by Pull-Through of the Right Colon - Ahmad, Hira; Vilanova-Sánchez, Alejandra; Amengual, Isabel; Guerra-Pastrian, Laura; Garrido-Pontnou, Marta; Montalvo, Cristina; Bueno, Alba; Langer, Jacob; Wood, Richard J.; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2021)
Hirschsprung disease is the most common neurocristopathy in children, resulting in the congenital loss of enteric ganglia. Rare reports of skip lesions have previously been reported in the literature. We present a case of skip lesions known prior to surgery and managed by pull-through of the right colon that allowed the preservation of the colon.
Keywords: calretinin stain; reoperation; enterocolitis; continence; aganglionosis